THE INFLUENCE OF RESOURCE BASED VIEW, STRATEGIC MANAGEMENT INFORMATION SYSTEM ON PERFORMANCE OF PERSONNEL IN INFORMATION INTELLIGENCE TECHNOLOGY IN STATE INTELLIGENCE AGENCY MEDIATED IN STRATEGIC POLICY - Purwanto, Bambang; Husini, Zulkifli; Anggiani, Sarfilianty; Kusnadi (International Journal of Research -GRANTHAALAYAH, 2022)
This research is aimed at the interests of the Organization of the State Intelligence Agency, especially the Deputy for Information Technology, which is the implementing element of some of the tasks and functions of the State Intelligence Agency in the Field of Technology Intelligence who is directly responsible to the Head of the State Intelligence Agency. The Deputy for Technology Intelligence has the task of carrying out policy formulation and implementation of Information Technology intelligence activities and/or operations. The method of analysis is done through explanatory research, with the application of PLS/SEM. Concepts and problems under study look at causality, then explain the variables causing the problem under study. The research sample was 96 Staff and Officials of the Directorate of Planning for Control of Activities and Operations, the Directorate of Telematics, and the Directorate of Geospatial Intelligence at the State Intelligence Agency. The results of this study Resource Based View has a positive effect on Performance. Strategic Management Information System has a positive effect on Performance. Strategic Policy has a positive effect on Performance. illustrates that Resource Based View, Strategic Management Information System and Strategic Policy at the Deputy for Information Technology of the State Intelligence Agency can have an influence on the performance of the personnel of the State Intelligence Agency. Theoretical implications of the Strategic Policy through increasing its dimensions will be able to improve the performance of the Deputy for Information Technology of the State Intelligence Agency so as to increase the trust and loyalty of related parties. Resource Based View, and Strategic Management Information System The results of this study strengthen the positive and significant influence of Resource Based View, and Strategic Management Information System on Strategic Policy. Improvement and development of the quality of human resources must first, pay attention to policies and strategies. The development will give a good indication of the performance of the State Intelligence Agency personnel.